Irregular Sleep/Wake Patterns Are Associated With Reduced Quality of Life in Post-treatment Cancer Patients: A Study Across Three Cancer Cohorts - Trivedi, Ritu; Man, Hong; Madut, Ayey; Mather, Marius; Elder, Elisabeth; Dhillon, Haryana M.; Brand, Alison; Howle, Julie; Mann, Graham; DeFazio, Anna; Amis, Terence; Cain, Sean W.; et al. (Frontiers in Neuroscience, 2021)
Background: Cancer patients often describe poor sleep quality and sleep disruption as contributors to poor quality of life (QoL). In a cross-sectional study of post-treatment breast, endometrial and melanoma cancer patients, we used actigraphy to quantify sleep characteristics with a focus on sleep regularity (sleep regularity index, (SRI)) and examined relationships with reported sleep symptoms and QoL. Methods: Participants were recruited post-primary treatment (35 diagnosed with breast cancer, 24 endometrial cancer and 29 melanoma) and wore an actigraphy device for up to 2 weeks. Sleep metrics were calculated, including the sleep regularity index (SRI). Self-report questionnaires for sleep quality (Pittsburgh Sleep Quality Index (PSQI)), sleepiness (Epworth Sleepiness Scale (ESS)), insomnia symptoms (Insomnia Severity Index (ISI)), and cancer-related QoL (European Organisation for Research and Treatment of Cancer EORTC (QLQ-C30)) were then completed. Data were compared using ANOVA or Chi-Square tests. Multivariate linear regression analysis was used to determine independent variable predictors for questionnaire-derived data. Results: Age distribution was similar between cohorts, endometrial and breast cancer cohorts were predominantly female, as expected, and BMI was higher in the endometrial cancer cohort, followed by breast and melanoma (breast, 34/35 (97%) female, 62.1±9.5 years (mean±SD), BMI 28.4±5.7 kgm-2; endometrial 24/24 (100%) female, 62.5±9.1 years, 34.3±7.4 kgm-2; and melanoma (9/29 (31%) female, 59.5±11.8 years, 30.8±6.3 kgm-2). There were no differences between tumour groups in: total sleep time (breast 7.5±1.0 hours; endometrial 7.3±0.8 hours; melanoma 7.3±1.1 hours), sleep onset latency, bedtime, or SRI (breast 29.7±21.8 mins; endometrial 28.8±28.2 mins; melanoma 34.1±25.2 mins), and SRI (breast 80.9±8.0, endometrial 80.3±12.2, melanoma 81.4±7.0) (all p>0.05). A higher SRI was associated with both better functional and symptom scores, including increased global QoL, better physical functioning, less sleepiness and fatigue, better sleep quality, and associated with less fatigue, nausea/vomiting, dyspnea, and diarrhea (all p<0.05). Conclusions: In cancer patients post-treatment, greater sleep regularity is associated with reduced sleep symptoms and increased global QoL, as well as increased physical functioning and fewer cancer related symptoms. Clinical management strategies focused on improving sleep regularity may provide a pathway to better sleep and QoL outcomes for cancer patients.